Effects of grain refinement on age hardening behavior and precipitation kinetics of Al–Si–Cu–Mg alloys: Einfluss der Kornfeinung auf das Alterungsverhalten und die Ausscheidungskinetik von AlSiCuMg‐Legierungen. Issue 2 (23rd January 2017) - Lu, T.; Tao, S.; Chen, Y.; Pan, Y.; Pi, J.
Abstract : The influences of grain refinement on precipitation kinetics were investigated for an Al–11 wt% Si–1.5 wt% Cu–0.3 wt% Mg casting alloy doped with B and and with La–B respectively by microstructure observation, hardness test and Johnson–Mehl–Avrami (JMA) equation. Co‐alloying of La–B facilitates the faster hardening response with higher hardness value for the alloy. The calculated Avarmi exponent indicates that the nucleation of θ′‐Al2 Cu precipitates occurs on grain boundaries for the refined alloys. The activation energies for the precipitation are of 42 kJ/mol and 30 kJ/mol for B‐doped and La–B co‐doped alloys, respectively.